Escaping the "Polluter Pays” Trap - Financing Wastewater Treatment on the Tijuana-San Diego Border - Itay Fischhendler (European Regional Science Association (ERSA), 2005)
Building and operating wastewater facilities to treat transboundary effluents requires dividing the cost of pollution prevention between the bordering states. When cost-sharing questions arise, the solution often suggested is the "polluter pays principle” (PPP). However, when political and economic relations between neighboring countries are asymmetrical the effectiveness of the PPP to resolve the wastewater problem is not clear. This paper argues that implementing the PPP ignores many of the existing asymmetries between the different sides, including asymmetries in power, willingness and ability to pay for wastewater treatment and operational capacities. As a result, the PPP's ability to provide adequate wastewater treatment is hampered. In response, neighboring countries sometimes replace the PPP with other cost-sharing arrangements that offset, to some degree, the existing asymmetries, thereby creating a more politically feasible and institutionally sustainable water pollution regime. Among these alternative principles are "beneficiary pays the difference" and "equal division of the cost burden" of wastewater treatment. This implies that it is not enough for a cost-sharing principle to be fair; it also has to offset, at least in part, the existing asymmetries otherwise the regime set will not be sustainable and thus economically viable. This is the focus of analysis in this paper, to which is added an historical perspective of the cost-sharing evolution of the pollution prevention regime along the San Diego/Tijuana border over the last century.
Keywords: 330